2023
DOI: 10.1021/acsapm.2c02033
|View full text |Cite
|
Sign up to set email alerts
|

Truxene-Based Porous Triazole-Linked Polymers for Dye Removal through Synergetic Adsorption and Photodegradation

Abstract: Two high surface area porous polymers (TxTri and PhTxTri) consisting of semiconducting truxene units connected through triazole nodes have been synthesized via Cu(I)-catalyzed azide−alkyne click polymerization, and their ability to remove different organic dyes (Nile blue, Rhodamine B, and Methyl orange) from aqueous solutions has been investigated. The presence of triazole moieties in the polymer walls, capable of binding guest molecules through different intermolecular interactions (such as dipole−dipole int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…[17][18][19][20] We have previously reported different truxene-based polymers that show interesting photocatalytic activity in reactions such as water splitting, oxidative photodegradation or amines homocoupling. [21][22][23] We have also found that truxene-based polymers can be used as sensors of nitroaromatic compounds through a fluorescence quenching mechanism and have established that the connectivity position of the monomers has important implications for their sensing capability. [24] In an attempt to optimize the performance and move towards practical application of truxene-related polymers, in this manuscript we introduce four new donor-acceptor polymers synthesized by connecting electron-rich semiconducting C 3symmetric truxene monomers or its triaza triindole analog with an electron-deficient C 2 -symmetric benzothiadiazole (BTD) comonomer, either through the 2,7,13 or 3,8,13 positions.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…[17][18][19][20] We have previously reported different truxene-based polymers that show interesting photocatalytic activity in reactions such as water splitting, oxidative photodegradation or amines homocoupling. [21][22][23] We have also found that truxene-based polymers can be used as sensors of nitroaromatic compounds through a fluorescence quenching mechanism and have established that the connectivity position of the monomers has important implications for their sensing capability. [24] In an attempt to optimize the performance and move towards practical application of truxene-related polymers, in this manuscript we introduce four new donor-acceptor polymers synthesized by connecting electron-rich semiconducting C 3symmetric truxene monomers or its triaza triindole analog with an electron-deficient C 2 -symmetric benzothiadiazole (BTD) comonomer, either through the 2,7,13 or 3,8,13 positions.…”
Section: Introductionmentioning
confidence: 86%
“…Considering the good photocatalytic activity previously shown by truxene-based polymers [21][22][23] we have explored their potential interest in the photocatalytic detoxification of chemical agents such as the mustard gas (MG). Experiments were performed on the less toxic simulant 2-chloroethyl ethylsulfide (MGS) under blue LED light and an oxygen balloon (Scheme 2).…”
Section: Photocatalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…5 Therefore, developing cost-effective materials and techniques for the sequestration of toxic contaminants from water has gained significant research priority in recent years. 6 Several strategies were developed and reported in the recent past to purify water, such as adsorption, 7,8 photodegradation, 9,10 electrochemical oxidation, 1 etc. Among these, adsorption has been regarded as one of the simplest, most efficient, and cost-effective ways for the separation of trace contaminants from water.…”
Section: Introductionmentioning
confidence: 99%